2013
DOI: 10.2478/s11536-013-0155-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors in patients with herpes zoster infections: case-control study

Abstract: AbstractThe aim of this study was to determine the prevalence of chronic disease and the risk factors for herpes zoster infection. In this case-control study medical records were collected from 55 patients who presented with herpes zoster and 54 patients in a control group who presented with gastroenterocolitis. Both groups were treated at the Clinic for Infectious Diseases, University Clinical Hospital Mostar from January, 2005 to December, 2010. When we compared the herpes zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…A decreased relative risk of zoster among smokers (particularly current smokers) have been reported in several studies ( 7 – 12 ), whereas no association was found in others ( 13 18 ). In a single, small case–control study, researchers reported an association with alcohol consumption (odds ratio = 3.8) ( 16 ); otherwise, no substantial associations with zoster have been observed for alcohol consumption ( 7 , 8 , 14 , 16 , 17 ), body mass index (BMI) ( 7 , 8 , 14 , 17 , 19 ), or physical activity ( 8 ). Interpretation of existing evidence is hampered by crude categorization of exposures; particularly, there is a lack of dose–response analyses.…”
Section: Abbreviationsmentioning
confidence: 99%
“…A decreased relative risk of zoster among smokers (particularly current smokers) have been reported in several studies ( 7 – 12 ), whereas no association was found in others ( 13 18 ). In a single, small case–control study, researchers reported an association with alcohol consumption (odds ratio = 3.8) ( 16 ); otherwise, no substantial associations with zoster have been observed for alcohol consumption ( 7 , 8 , 14 , 16 , 17 ), body mass index (BMI) ( 7 , 8 , 14 , 17 , 19 ), or physical activity ( 8 ). Interpretation of existing evidence is hampered by crude categorization of exposures; particularly, there is a lack of dose–response analyses.…”
Section: Abbreviationsmentioning
confidence: 99%
“…It is believed that reactivation is the result of reduced cellular immunity specific to VZV, and periodic exposure to people with varicella or herpes zoster will enhance cell-specific immunity against VZV characterized by periodic subclinical reactivation. Many studies have shown no pattern of herpes zoster season, while other studies suggest a higher incidence in summer in the middle of the year, as a consequence of increased exposure to ultraviolet light [5,6]. The results of Wu et al study found an increase in HZ incidence very strongly associated with UV.…”
Section: Discussionmentioning
confidence: 96%
“…The results of Wu et al study found an increase in HZ incidence very strongly associated with UV. Recent research has reported an increase in the incidence of HZ in summer in countries with several different seasons of the year, this pattern is associated with UV peak summer exposure and possibly a HZ trigger [5][6][7]10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no difference in the risk of head and neck, musculoskeletal, and viral infections in patients with diabetes and patients without, although a few studies have found an increased risk of these types of infections [4, 10, 3740]. …”
Section: Discussionmentioning
confidence: 99%